Identification of new modulator of DNA repairing pathways based on natural product (±)-peharmaline A - Kulkarni, Akshay S.; Dash, Anshurekha; Shingare, Rahul D.; Chand, Jagdish; Manhas, Diksha; Singh, Aman; Nandi, Utpal; Goswami, Anindya; Reddy, D. Srinivasa (Bioorganic & Medicinal Chemistry, 2023)
The complex heterogenic environment of tumour mass often leads to drug resistance and facilitate chemo insensitivity triggering more malignant phenotypes among cancer patients. Major DNA-damaging cancer drugs have been consistently proven unsuccessful in terms of elevating chemo-resistance. (& PLUSMN;)-peharmaline A, a hybrid natural product isolated from seeds of Peganum harmala L. possesses significant cytotoxic activities. Herein, we have described the design, and synthesis of a novel library of close and simplified analogues around the anticancer natural product (& PLUSMN;)-peharmaline A and investigated their cytotoxic activities, which led to the identification of three structurally simplified lead compounds exhibiting better potency than parent natural product. Among them, demethoxy analogue of peharmaline A was further investigated for its anticancer potential eliciting demethoxy analogue as potent DNA-damage inducing agent attenuating the expression of the proteins responsible for the DNA damage repair. Therefore, this demethoxy analogue warrants detailed investigations for the confirmations of the molecular mechanism-based studies responsible for its anticancer activity.
Keywords: DNA damage; EMT; Pictet; Spengler reaction; Structure-activity relationship; Total synthesis

Interplay between genotoxic stress and STING activation in cellular senescence and inflammatory responses - Dash, Anshurekha; Kulkarni, Akshay S.; Irshad, Faisal; Masal, Dattatraya P.; Manhas, Diksha; Nandi, Utpal; Reddy, D. Srinivasa; Goswami, Anindya (International Immunopharmacology, 2025)
STING pathway is activated by endogenous or exogenous DNA damage and is known to trigger cell-intrinsic innate immunity. In this study, we demonstrated that the Peharmaline analog NDS101781 is a potent genotoxic molecule to trigger cellular senescence via innate immune-responsive STING activation. We found NDS101781 consistently modulated the expression of DDR markers including gamma-H2AX, Rad51, PARP1, ATM and MRE11 in breast cancer cells with concomitant amplification in the hallmarks of senescence along with STING signaling mediators which is intricately involved in NDS101781-mediated senescence activation as evidenced by significant reduction in the senescent population in si-TMEM173-transfected cells. In vitro findings proclaimed that STING activation by NDS101781 is crucial for p21-mediated senescence augmentation, a process regulated by ATM and p53 via a pathway independent of cGAS. Although STING is activated by both canonical and non-canonical manner, our mechanistic findings indicated that ATM played a crucial role in early activation of NDS101781 driven STING signaling via p53 activation and stimulation of pTBK1, NF-kappa B, and p-IRF3, through a non-canonical cascade in cGAS-independent mechanism. The results also indicated that interference of canonical and non-canonical STING activation, responsible for NF-kappa B stimulation leading to IL-6 generation. Intriguingly, the inhibition of ATM diminished senescence hallmarks; however, suppression of ATM as well as p21 neutralization triggered apoptotic cascade and thus regulating the SASP factors. However, transient knockdown of p21 moderately instigated the apoptotic mediators underscoring that NDS101781 mediated senescence induction delayed programmed cell death under intact p21 conditions. Moreover, pharmacokinetics of NDS101781 confirmed its excellent half-life in a preclinical model and in vivo studies confirmed that NDS101781 significantly inhibited tumor growth in a syngeneic aggressive 4T1-p53 breast cancer model.
Keywords: ATM; IL-6; Peharmaline; Senescence; STING